A Polymer–(Tandem Drugs) Conjugate for Enhanced Cancer Treatment. Issue 6 (7th January 2013) - Zhou, Dongfang; Xiao, Haihua; Meng, Fanbo; Li, Xiaoyuan; Li, Yuxin; Jing, Xiabin; Huang, Yubin
<x xml:space="preserve">Abstract</x> A novel strategy for combination chemotherapy (platinum and demethylcantharidin) via a polymer–(tandem drugs) conjugate for enhanced cancer treatment is demonstrated. Cisplatin can be released inside cell by reduction to attack DNA, while DMC will be hydrolyzed subsequently to block DNA‐damage‐induced defense mechanisms by serine/threonine phosphatase PP2A inhibition. Synergistic effect of the polymer–(tandem drugs) conjugate causes complete suppression of H22 liver tumor xenografts without recurrence. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>